WTO Dispute Settlement and Intellectual Property Disputes: Tracing the Trends and Implications - Islam, Mohammad Towhidul; Tasnim (Indonesian Journal of Law and Society, 2025)
Instead of a set of non-binding General Agreement on Tariffs and Trade (GATT) mechanisms, the Marrakesh agreement, the founding treaty of the World Trade Organization (WTO), instituted a binding framework for global trade disputes. WTO integrates a diverse array of dispute resolution mechanisms, both judicial and extrajudicial, along with essential authority to address trade and business matters, especially intellectual property disputes. Although this mechanism is relatively new, it has demonstrated an increasing number of IP matters being resolved. Involvement of major economies, good faith of the countries to implement and rectify actions, and speedy disposal of IP conflicts are commendable achievements of this body. However, it also poses some inevitable challenges of power imbalances, dependency on party bona fides and limitations in enforcement forces. With the proliferation of IP rights consciousness and its importance in world trade, this article uncovers how the WTO dispute settlement mechanism is navigating through the IP field. It assesses how effectively the WTO resolves disputes raised before it and what impacts the dispute settlement mechanism are making. This paper examines the role of WTO assessing the system’s strengths and weaknesses. It initially builds upon the basis by detailing the dispute settlement mechanism to resolve trade disputes, particularly IP ones. The discussion then changeovers to a case study approach to assess the mechanism’s role, followed by a critical analysis. Lastly, the paper scrutinizes the encounters prevailing in the system and tends to find probable actions required to unravel them for improvement.